STRESS DAN COPING STRATEGY KARYAWAN DI MASA PANDEMI COVID-19 - Tria Annisa; Anissa Lestari Kadiyono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The corona virus or Covid-19 has spread to all corners of the world including Indonesia in a fast time. In an effort by the government to minimize the spread, a work from home policy was adopted. But not so with Social Security Program Company which is engaged in services. This study aims to conduct an analysis of stress and coping strategies that can provide benefits in the form of an understanding of how employees of Social Security Program Company gave an assessment of the necessity of working in an office during the pandemic. Cognitive understanding of stress conditions and coping strategies that will be done will contribute to the company on how employees assess the necessity of working in pandemic conditions. A total of two employees were offered semi-structured research. The data obtained were analyzed by coding. The results of the study said that working in an office causes stressful conditions for employees. Employees coping strategy to solve it. More employees use problem focused coping than emotional focused coping. One respondent used the positive reappraisal process in dealing with stressful conditions.